Korelacje między religijnością a poczuciem sensu życia młodzieży szkół ponadgimnazjalnych w Poznaniu w świetle koncepcji Viktora E. Frankla i Dirka Hutsebauta - Machalski, Jędrzej (Humaniora. Czasopismo Internetowe, 2019)
Viktor Emil Frankl is considered to be a pioneering researcher into the issue of the meaning of life. He carried out a thorough analysis of the theories of his predecessors, and coined his own existential analysis and logotherapy, which have become some of the most popular trends in psychotherapy. Searching for the sources of the motivation for human action, one cannot ignore the phenomenon of religiosity. Over time, due to progressive secularization, it has become impossible to describe the religiosity of man through the existing categories. David M. Wulff laid the theoretical foundation for a new way of looking at religion. On the basis of Wulff’s theories, Dirk Hutsebaut distinguished four approaches to the Christian religion. His model of religiosity enables us to distinguish the types of faith and the ways of thinking about religion, also taking into account non-believers. This article, shows the correlation between religiosity and the sense of meaning of life in adolescents.